2015
DOI: 10.1021/acs.energyfuels.5b00742
|View full text |Cite
|
Sign up to set email alerts
|

Study of Biodiesel Blends on Emission and Performance Characterization of a Variable Compression Ratio Engine

Abstract: This study explores the emission of different pollutants using different blends in a variable compression ratio (VCR) engine. Biodiesel synthesized from Jatropha oil using a heterogeneous catalyst was investigated for emission analysis on a single-cylinder VCR engine with various blending ratios as well as load. Blends (biodiesel + diesel) of JB00, JB10, JB20, JB30, and JB100 were prepared at 40°C. The emission parameters, such as nitrogen oxides (NO x ), carbon monoxide (CO), and hydrocarbon (HC), were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The changes of exhaust gas temperature values depending on the engine speed of ED, biodiesels and fuel blends are shown in Figure 6. Biodiesel usage usually improves CO emissions and increases CO2 and NOx emissions due to higher combustion temperature and extra oxygen content in the chemical composition [17]. As a result of the performed tests, it was found that maximum CO emissions occurred at low engine speeds and CO emissions decreased depending on the engine speed rises (Figure 7).…”
Section: Exhaust Emissionsmentioning
confidence: 94%
“…The changes of exhaust gas temperature values depending on the engine speed of ED, biodiesels and fuel blends are shown in Figure 6. Biodiesel usage usually improves CO emissions and increases CO2 and NOx emissions due to higher combustion temperature and extra oxygen content in the chemical composition [17]. As a result of the performed tests, it was found that maximum CO emissions occurred at low engine speeds and CO emissions decreased depending on the engine speed rises (Figure 7).…”
Section: Exhaust Emissionsmentioning
confidence: 94%
“…Higher compression ratios enhance the combustion and thus nitrogen oxides emissions significantly elevates due to higher in-cylinder temperature and higher flame velocity. Biodiesel usage usually improves CO emissions and increases CO 2 and NO x emissions due to higher combustion temperature and extra oxygen content in the chemical composition [26].…”
Section: Emission Characteristicsmentioning
confidence: 99%
“…For biodiesel-alcohol blends, the maximum increment was observed with B95E5 fuel as 7,94% compared to biodiesel at 16:1 CR. The main reason of these trends may be due to improved combustion of diesel-alcohol and biodiesel-alcohol blends [19].…”
Section: Emission Characteristicsmentioning
confidence: 99%